Comparison of load responsiveness of cartilage T1rho and T2 in porcine knee joints: an experimental loading MRI study. Issue 10 (October 2015) - Hamada, H.; Nishii, T.; Tamura, S.; Tanaka, H.; Wakayama, T.; Sugano, N.
Summary: Objective: To compare changes in T1rho and T2 values of the femoral cartilage in porcine knee joints under staged loading and unloading conditions. Design: Sixteen porcine knee joints with intact capsules and surrounding muscle were imaged using a custom-made pressure device and 3.0 T magnetic resonance imaging. Sagittal T1rho and T2 images were obtained for the lateral and medial condyles under the following compression loads: none (Load 0), 140 N (Load 140), 300 N (Load 300), and no compression after decompression (Post-load). The percentage changes of cartilage T1rho and T2 values under each loading condition from those at Load 0 were calculated for weight-bearing overall and eight subdivided regions of interest (ROIs) in both femoral condyles. The actual contact pressure under Load 140 and Load 300 was measured using pressure-sensitive film. Results: For the overall ROI, the mean decreases of T1rho and T2 values were 4.4% and 5.1% under Load 140% and 10.9% and 10.6% under Load 300 in the medial condyle and were 5.2% and 4.0% under Load 140% and 10.6% and 6.0% under Load 300 in the lateral condyle. In the medial condyle, the actual contact pressure correlated highly with percentage changes in T1rho ( r = −0.84, P < 0.01) and T2 ( r = −0.79, P < 0.01), but those correlations were relatively low in the lateral condyle. Conclusion: Although there were side-dependent variations in the correlations with actual pressure, cartilage T1rho and T2 showed similarly sensitive responses to applied load.